The impact of Bt cotton adoption on the stability of pesticide use - Fang-bin QIAO; Ji-kun HUANG; Shu-kun WANG; Qiang LI (Journal of Integrative Agriculture, 2017)
Abstract: Even though the impact of Bacillus thuringiensis (Bt) cotton on pesticide use has been well documented, all previous studies focus on the mean value of pesticide use. Using seven unique waves of panel data collected between 1999 and 2012 in China, we show that Bt cotton adoption has not only caused a reduction of the mean value of pesticide use, but also a reduction of the standard deviation of pesticide use. We conclude that Bt technology adoption has also contributed to the stability of pesticide use in cotton production. We believe that this contribution is theoretically and practically relevant because of the long length of our unique dataset.